Report from the 1st Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes & Cardiovascular Disease (D&CVD) EASD Study Group - Schnell, Oliver; Standl, Eberhard; Catrinoiu, Doina; Genovese, Stefano; Lalic, Nebojsa; Skra, Jan; Valensi, Paul; Ceriello, Antonio (Cardiovascular diabetology, 2016)
The 1st Cardiovascular Outcome Trial (CVOT) Summit of the Diabetes & Cardiovascular Disease (D&CVD) EASD Study Group was held during the annual meeting on 30 October 2015 in Munich. This summit was organized in light of recently published and numerous ongoing CVOTs on diabetes, which have emerged in response to the FDA and the EMA Guidelines. The CVOT Summit stands as a novel conference setup, with the aim of serving as a reference meeting for all topics related to CVOTs in diabetes. Members of the steering committee of the D&CVD EASD Study Group constitute the backbone of the summit. It included presentations of key results on DPP-4 inhibitors, GLP-1-Analogues, SGLT-2 inhibitors, acarbose and insulins. Diabetologists' and cardiologists' perspective on the potential need of new study designs were also highlighted. Furthermore, panel discussions on the design of CVOTs on diabetes were included in the program. The D&CVD EASD Study Group will continue its activity. In-depth discussions and presentations of new CVOTs like LEADER, will be resumed at the 2nd CVOT on diabetes of the D&CVD EASD Study Group, which will be held from 20-22 October 2016 in Munich ( http://www.dcvd.org).
Keywords: rizikové faktory; kardiovaskulární nemoci; klinické zkoušky jako téma; diabetes mellitus; Diabetes Mellitus; hypoglykemika; lidé; Clinical Trials as Topic; Research Design; Risk Factors; Hypoglycemic Agents; Cardiovascular Diseases; výzkumný projekt; Humans